2003
DOI: 10.1046/j.1365-3016.2003.00468.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal factors associated with the duration of breast feeding in Jeddah, Saudi Arabia

Abstract: Recently, there has been increasing concern about the decline in breast-feeding pattern in developing countries. The objectives of this study were to document the recent breast-feeding trends in Jeddah during the first year of an infant's life and identify the probable maternal risk factors implicated in breast-feeding cessation. Data were collected from six randomly selected primary health care centres in Jeddah City. All married women with an infant Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
47
1
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 25 publications
7
47
1
4
Order By: Relevance
“…For assessment of factors associated with breastfeeding cessation at 6 months of age we used multivariate Cox regression analyses. A total of 21 variables were included in the final model that was constructed using factors that had an association with breastfeeding duration based on the univariate association (the level of significance was set at P < 0.05), as well as factors reported to influence breastfeeding initiation and duration from previous studies (5,6,(8)(9)(10) and that were considered to potentially affect breastfeeding practice in our local region.…”
Section: Discussionmentioning
confidence: 99%
“…For assessment of factors associated with breastfeeding cessation at 6 months of age we used multivariate Cox regression analyses. A total of 21 variables were included in the final model that was constructed using factors that had an association with breastfeeding duration based on the univariate association (the level of significance was set at P < 0.05), as well as factors reported to influence breastfeeding initiation and duration from previous studies (5,6,(8)(9)(10) and that were considered to potentially affect breastfeeding practice in our local region.…”
Section: Discussionmentioning
confidence: 99%
“…[13] Despite the great advances in health services in Saudi Arabia, studies have reported a downward trend in breast-feeding practice. [6,11,[14][15][16] In this study, 75.4% of women initiated breast-feeding after delivery. However, only 18.5% were exclusively breast-fed.…”
Section: Discussionmentioning
confidence: 99%
“…Using sample size online calculator (Raosoft), total population 200, expected prevalence according to nearest study to be 54% at sixth month, [11] confidence level 95%, and the margin of error 10%, the estimated sample size was 65. Using systematic random sampling technique, every third child was selected by systematic random sampling technique.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have reported that caesarean section delivery was a risk factor for not initiating breastfeeding, and that infants delivered by caesarean section started suckling later and were given bottles more often during the first days of life. This, in addition to lack of antenatal and postnatal education to guide the mother into initiating lactation and maintaining it through regular and extensive breastfeeding, certainly influences the infant's feeding pattern (13) . The present study reveals that the highest percentage (73.3%) did not have any advices or instructions about breastfeeding (23.3%) the family & mother was a source of knowledge about breastfeeding.…”
Section: Discussionmentioning
confidence: 99%